Perturbed structural dynamics underlie inhibition and altered efflux of the multidrug resistance pump AcrB - Eamonn Reading (Nature Portfolio, 2020)
AcrB is a prototypical resistance–nodulation–division (RND) bacterial transporter, conferring resistance to a variety of antibiotics. HDX-MS and other, complementary approaches offer insight into AcrB structural dynamics and suggest the molecular mechanisms underlying drug export and inhibition of this multidrug-resistance conferring pump.